Hubungan Kekerabatan Kepiting Rajungan (Portunus sp.) Berdasarkan DNA Barcoding di Perairan Percut Sei Tuan Kabupaten Deli Serdang - Zuhra, Arini; Manalu, Kartika; Idami, Zahratul (Universitas Cokroaminoto Palopo, 2024)
Rajungan crab (Portunus sp.) is one type of crab that has a fairly high commodity value, this species has a fairly wide distribution covering the Indo-Pacific Ocean and also offshore, this crab has an important role in ecological stability. Portunus sp. has a more attractive appearance compared to other crabs. The purpose of this study is to look at the (dominant) crab species found in January (west wind season) in the waters of Percut Sei Tuan based on the genes CO1, and phylogenetics (kinship relationship) of Portunus sp. in the waters of Percut with Portunus sp. in NCBI or Genebank. The method used in this study is DNA isolation on specimens using the Favorgen kit locus of the CO1 gene in the genome of the Portunus sp. amplified by PCR technique with LCO1940 (forward) and HCO2198 (reverse) primers. The results of the research that have been carried out have found 3 species from the genus Portunus, namely P. sanguinolentus, P. trituberculatus and P. pelagicus. Of the three species found in the Percut Sei Tuan Waters, P. trituberculatus and P. pelagicus have a closer kinship relationship compared to P. sanguinolentus, based on the percentage of AT content and GC content, the AT content is higher at 61.03% which means that the three species have primitive properties. The genetic distance between P. sanguinolentus and P. trituberculatus is closer (19.32) compared to P. pelagicus. Based on the phylogenetic tree reconstruction, P. trituberculatus and P. sanguinolentus are closer to P. pelagicus with the Neighbor-Joining method and the Kimura-2-Parameter calculation model. Thus, it can be concluded that DNA barcoding using the CO1 gene locus can be used as a method in identifying Portunus sp. molecularly and kinship relationships with other species.